Science in Movements Knowledge Control and Social Contestation in China's Hydropower, GMO and Nuclear Controversies - Jia, Hepeng (Chinese Perspectives on Journalism and Communication, 2022)
This book analyses and compares the origins, evolutionary patterns and consequences of different science and technology controversies in China, including hydropower resistance, disputes surrounding genetically modified organisms and the nuclear power debate. The examination combines social movement theories, communication studies, and science and technology studies. Taking a multidisciplinary approach, the book provides an insight into the interwoven relationship between social and political controls and knowledge monopoly, and looks into a central issue neglected by previous science communication studies: why have different controversies shown divergent patterns despite similar social and political contexts? It is revealed that the media environment, political opportunity structures, knowledge-control regimes and activists' strategies have jointly triggered, nurtured and sustained these controversies and led to the development of different patterns. Based on these observations, the author also discusses the significance of science communication studies in promoting China's social transformation and further explores the feasible approach to a more generic framework to understand science controversies across the world. The book will be of value to the academics of science communication, science and technology studies, political science studies and sociology, as well as general readers interested in China's science controversies and social movements. The Open Access version of this book, available at http://www.taylorfrancis.com/books/e/9781003160212, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.